Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2025)
Table of Content:• The Impact of Job Security on Contextual Performance: An Applied Study of Workers  in the Bish Municipality in the Kingdom of Saudi ArabiaMs. Hawaz Abdolaziz Essa ,Prof. Alariki Baseim Qaid• Rooting Administrative Functions in The Light of The Holy Qur’an and The Sunnah: A Comparative Study with Modern Administrative Thought to Build an Integrated Islamic Administrative ModelDr. Najla Farhat Alakroot• The impact of organizational behavior on the effectiveness of the organizational role of The Ministry of Health branch in achieving the goals of health transformation in Najran regionMr. Faisal Hussain Faisal Alsharif,  Dr. Ali Mohammed Al Mansour ,Mr. Manassar Zaied M. Al Sulieman• The Impact of Knowledge Management Processes in Improving The Quality of Decisions in The Palestinian Ministry of Finance - The Southern GovernoratesDr. Mahmoud Mohammed Abu Aisha, Prof. Yousif Hussein Ashour ,Mr. Haytham Ahmed Al-Slakhi• Use of Artificial Intelligence (AI) Applications and Creative Behavior among Employees of the Education Department in Jeddah Governorate from their PerspectiveMs. Hoda Salah Musaed Al-Jahni• The Role of Strategic Planning in Improving Engineering Project Performance According to Saudi Vision 2030 " Case Study - Projects by Dar Al-Handasah"Eng. Nazar Mohamed Elkheir• The Mediating Role of Practical Relevance between Instructional Practices of Teachers and Sustainable Engagement among Accounting Students in Saudi Arabia: The Moderating Role of Artificial Intelligence UsageAsst-Prof. Warda Hodaed Alsheikh
Keywords: The Journal of Economic, Administrative and Legal Sciences